On the trail of Mycobacterium avium subsp. paratuberculosis and Mycobacterium bovis in mainland Portugal: a microbiological and molecular survey in wildlife - Reis, Ana Cristina Lopes dos (2016)
Tese de mestrado em Biologia Molecular e Genética, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2015